2010
DOI: 10.1016/j.bbapap.2009.07.008
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase Family X: Function, structure, and cellular roles

Abstract: The X Family of DNA polymerases in eukaryotic cells consists of Terminal Transferase, and DNA polymerases β, λ, and μ. These enzymes have similar structural portraits, yet different biochemical properties, especially in their interactions with DNA. None of these enzymes possesses a proofreading subdomain, and their intrinsic fidelity of DNA synthesis is much lower than that of a polymerase that functions in cellular DNA replication. In this review, we discuss the similarities and differences of three members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
151
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(154 citation statements)
references
References 178 publications
(258 reference statements)
1
151
0
Order By: Relevance
“…As a key enzyme involved in DNA base excision repair, pol ␤ has been implicated in CAG repeat expansion during the repair of oxidative damage that occurs within CAG repeats (15). Previous studies have also shown that pol ␤ can bypass a number of different types of lesions in the template strand, including cisplatin adducts, cyclobutanol pyrimidine dimers, and 6 -4 photoproducts (34). We demonstrate here that pol ␤ can also "bypass" a (CAG) n / (CTG) n hairpin lesion, but the "bypass" in our study occurs in the primer strand, leading to expansion of the repeats.…”
Section: Discussionmentioning
confidence: 99%
“…As a key enzyme involved in DNA base excision repair, pol ␤ has been implicated in CAG repeat expansion during the repair of oxidative damage that occurs within CAG repeats (15). Previous studies have also shown that pol ␤ can bypass a number of different types of lesions in the template strand, including cisplatin adducts, cyclobutanol pyrimidine dimers, and 6 -4 photoproducts (34). We demonstrate here that pol ␤ can also "bypass" a (CAG) n / (CTG) n hairpin lesion, but the "bypass" in our study occurs in the primer strand, leading to expansion of the repeats.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some types of DNA damage, such as cisplatin-induced lesions, are repaired more slowly in human cells than in chimpanzee cells, which is consistent with the hypothesis of downregulation of repair in humans (Weis et al 2008). Pol b is capable of error-prone bypassing of several types of DNA lesions, including 8-oxo-7,8-dihydrodeoxyguanine, cisplatininduced lesions, and UV-induced lesions (Yamtich and Sweasy 2009). Overexpression of Pol b is associated with an increase in the mutation rate (Chan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Pol b is a 335-amino-acid, 39-kDa polymerase encoded by the POLB locus after the splicing of its 14 constitutive exons (Uchiyama et al 2009;Yamtich and Sweasy 2009). Pol b is a member of the X-family of DNA repair polymerases, plays a key role in base excision DNA repair, and its absence leads to sensitivity to methylating agents (Yamtich and Sweasy 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a systematic and thorough analysis of the roles of residues remote from the active site in DNA polymerase b has identified residues that are important for nucleotide selection and template alignment [Yamtich and Sweasy, 2010]. As one example, a triad of residues Arg333 Glu316 Arg182 in the fingers domain of pol b may disrupt packing of side chains in the hinge region and therefore alter the conformational change required for efficient DNA replication [Murphy et al, 2011].…”
mentioning
confidence: 99%